An Integrated Approach in the Assessment of the Vlasina River System Pollution by Toxic Elements - Sakan, Sanja; Mihajlidi-Zelić, Aleksandra; Škrivanj, Sandra; Frančišković-Bilinski, Stanislav; Đorđević, Dragana (Frontiers in Environmental Science, 2022)
Increasing pollutant levels in surface water are a very important problem in developing countries. In Serbia, the largest rivers are transboundary rivers that are crossing the border already polluted. Taking this into account, evaluation of the distribution characteristics, ecological risk and sources of toxic elements in river water and surface sediments in the watercourses of Vlasina watershed is of great significance for the protection of water resources in Serbia. 17 sediment and 18 water samples were collected and analyzed by ICP-OES and ICP MS to determine micro- and macroelements contents. The geo-accumulation index (Igeo) was applied to determine and classify the magnitude of toxic element pollution in this river sediment. The contents of studied toxic elements were below water and sediment quality guidelines. For studied river water, results of PCA indicated the difference in behavior of Cr, Mn, Ni, Cu, and, As and V, respectively. Cluster analysis classified water samples according to As and Cu content. The PCA result showed that lead in river sediments had different behavior than other elements and can be associated mainly with anthropogenic sources. According to the degree of Igeo, the majority of sediments in Vlasina region were uncontaminated regarding studied toxic elements. The origin of elements is mostly from natural processes such as soil and rock weathering.